Communicative culture of the future specialist of a technical university and his personal development in modern realities - Nigmatillina Laysan (E3S Web of Conferences, 2021)
The important characteristics of a person and activity of future specialist are not only the possession of information, of professional activity technologies, but also of communicative culture, which provides going beyond the regulatory activities, ability to create and transfer values, provide personal development and competitiveness on the labor market. Today, a low level of speech culture leads to a decrease in the general culture of young people and, as a result, is an obstacle to further career development in any field. The problem generally affects such industries as construction, architecture, design, as they are among the most demanded professions on the international labor markets.